Effect of perceived government regulation on purchase intention for regional brand agricultural products: an empirical investigation of Qianjiang crayfish - Na Xu; Yanpu Zhao; Man Chen (Frontiers in Sustainable Food Systems)
The consumption of regional brand agricultural products (RBAPs) has increased dramatically in China in recent years. However, due to insufficient government regulation and consumer perceptions, many unsuccessful RBAPs still face unfavorable attitudes toward purchase. Based on the stimulus–organism–response (SOR) theory, this study examined the effect of perceived government regulation—comprising perceived government regulation of production support (GP) and perceived government regulation of consumer protection (GC)—on the intention to purchase RBAPs. This study employed a partial least squares-structural equation model to quantitatively analyze a sample of 289 consumers of a typical regional brand of Qianjiang crayfish. Findings revealed that GP and GC had direct effects on perceived quality. GP, but not GC, had a direct effect on purchase intention. Furthermore, perceived quality and consumer trust both played partial mediating roles in the association between GP and purchase intention, and both fully mediated the relationship between GC and purchase intention. These findings are important for identifying and clarifying the effects of existing regulations to aid in promoting consumers’ purchase intention and facilitating the long-term sustainable development of public regional brands.